Gut resistome profiling reveals high diversity and fluctuations in pancreatic cancer cohorts - Liu, Xudong; Li, Kexin; Yang, Yun; Cao, Dingyan; Xu, Xinjie; He, Zilong; Wu, Wenming (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Pancreatic cancer is one of the most deadly cancer, with a 5-year overall survival rate of 11%. Unfortunately, most patients are diagnosed with advanced stage by the time they present with symptoms. In the past decade, microbiome studies have explored the association of pancreatic cancer with the human oral and gut microbiomes. However, the gut microbial antibiotic resistance genes profiling of pancreatic cancer patients has never reported compared to healthy cohort. Results: In this study, we addressed the gut microbial antibiotic resistance genes profile using the metagenomic data from two online public pancreatic cancer cohorts. We found a high degree of data concordance between the two cohorts, which can therefore be used for cross-sectional comparisons.Meanwhile, we used two strategies to predict antibiotic resistance genes and compared the advantages and disadvantages of these two approaches. We also constructed microbe-antibiotic resistance gene networks and found that most of the hub nodes in the networks were antibiotic resistance genes. Conclusions: In summary, we describe the panorama of antibiotic resistance genes in the gut microbes of patients with pancreatic cancer. We hope that our study will provide new perspectives on treatment options for the disease.Keywor ds: Pancreatic cancer; gut microbiomes; antibiotic resistance genes; vancomycin-resistant genes; public pancreatic cancer cohorts 1. Intr oduction Pancreatic cancer, particularly pancreatic ductal adenocarcinoma (PDAC), is one of the most deadly cancer, with a 5-year overall survival rate of 11% (Siegel, et al., 2022). The high lethality of PDAC is attributed to both late diagnosis and limited therapeutic options. This is because symptoms are often nonspecific and only become apparent in the advanced stages of the disease, when tumors may already be locally non-resectable or have metastasized. Surgery is the only potential curative treatment, but this method is only possible in the early stage. Combinatorial chemotherapy remains the standard of care for PDAC patients, but most patients present with an advanced disease characterized